Research on the Technology of Computer Network Security Protection - Peng, Yue (Bright Publisher, 2023)
The continuous deepening of the number and importance of sensitive and key info stored in computer network system has brought severe challenges to the computer cyber security protection tech. It is urgent to upgrade the cyber security protection, so that it can serve and match the healthy development of computer network. Based on this, this paper first analyses the concept and connotation of computer cyber security, then studies the main content of computer cyber security protection tech, and finally gives the computer cyber security protection measures.